Breaking molds: Oswaldella laertesi, sp. nov., a unique Antarctic species of Oswaldella Stechow, 1919 (Cnidaria: Hydrozoa: Kirchenpaueriidae) - Cantero, Alvaro L. Peña (Zootaxa, 2007)
A new species of the Antarctic genus Oswaldella Stechow is described and figured, and its position amongst the remaining species of the genus is discussed. The material was collected from the Ross Sea area (Antarctica) during the BioRoss survey of the western Ross Sea and Balleny Islands in 2004. Oswaldella laertesi, sp. nov., is unique amongst known species of the genus in having hydrocladia arranged in three longitudinal rows.